Summary and policy recommendations: Toward a nutrition revolution for Africa - Covic, Namukolo; Hendriks, Sheryl L. (International Food Policy Research Institute, 2016)
Malnutrition in all its forms—undernourishment, micronutrient deficiencies, and overweight—is robbing Africa of much-needed productivity and growth potential. Addressing nutrition is an investment with high potential returns in terms of reduced health costs, increased productivity, and improved human resource capacity and economic growth. Although nutrition interventions have been seen as belonging in the health sector, integrated programs that include agriculture and other sectors can create synergies and added value. The agriculture sector needs to become more nutrition sensitive so that it can work in tandem with other sectors to drive a much-desired nutrition revolution for Africa. Achieving the goals of the Malabo Declarations on (1) accelerated agricultural growth and transformation for shared prosperity and improved livelihoods and (2) nutrition security through inclusive economic growth and sustainable development will require efforts from agriculture, social agriculture, social protection, education, water and sanitation, and more to implement high-impact interventions at scale.